2010
DOI: 10.1007/s11064-010-0186-3
|View full text |Cite
|
Sign up to set email alerts
|

A Pharmacological Activator of AMP-Activated Protein Kinase Protects Hypoxic Neurons in a Concentration-Dependent Manner

Abstract: 5'adenosine monophosphate-dependent protein kinase (AMPK) is a member of metabolite-sensing kinase family which plays an important role in intracellular energy metabolism, particularly in the hypoxic neurons process. However, the effect of AMPK activation on hypoxic neurons remains controversial. In the present study, we report that the effect of AMPK activation induced by pretreatment with 5-aminoimidazole-4-carboxamide-1-b-4-ribofuranoside (AICAR) in neurons using the hypoxic model in vitro. The level of AMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Furthermore, we could establish the molecular mechanism responsible for carbimazole-mediated eEF2 phosphorylation, which includes AMPK-dependent activation of eEF2K. Interestingly, both kinases are associated with cytoprotective molecular mechanisms, including reduced hypoxic injury, stress resistance, autophagy, inhibition of plaque formation in Alzheimer's disease, regulation of energy homeostasis, and endothelial nitric oxide synthesis that improves blood flow in ischemic brain tissue (Hardie, 2004;Terai et al, 2005;Greco et al, 2009;Py et al, 2009;Li and McCullough, 2010;Zhang et al, 2010). However, whether carbimazole exerts all of these protective mechanisms remains to be established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we could establish the molecular mechanism responsible for carbimazole-mediated eEF2 phosphorylation, which includes AMPK-dependent activation of eEF2K. Interestingly, both kinases are associated with cytoprotective molecular mechanisms, including reduced hypoxic injury, stress resistance, autophagy, inhibition of plaque formation in Alzheimer's disease, regulation of energy homeostasis, and endothelial nitric oxide synthesis that improves blood flow in ischemic brain tissue (Hardie, 2004;Terai et al, 2005;Greco et al, 2009;Py et al, 2009;Li and McCullough, 2010;Zhang et al, 2010). However, whether carbimazole exerts all of these protective mechanisms remains to be established.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of eEF2K promotes cell survival, reduces hypoxic injury, and regulates autophagy in response to nutrient deprivation (Terai et al, 2005;Py et al, 2009). AMPK preserves energy homeostasis (Hardie, 2004) and attenuates ischemic cell damage (Zhang et al, 2010), inflammation (Salminen et al, 2011), arrhythmias (Wong et al, 2009), hypertrophy (Chan et al, 2004), structural remodeling (Du et al, 2008), and plaque formation in Alzheimer's disease (Greco et al, 2009). Additionally, it promotes neurogenesis, angiogenesis, and vascular function (Li and McCullough, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was shown that the AMPK inhibitor compound C was able protect neurons from tributyltin toxicity. Studies from another group showed that AICAR could protect rat primary cortical neurons from hypoxic death in a concentration-dependent manner [49]. Interestingly, whereas low doses were neuroprotective, higher doses lost their efficacy.…”
Section: Ampk and Cns Ischemic Strokementioning
confidence: 99%
“…These included the kinases AuroraA, Pim and AMPK. Of these AMPK has been shown to have an important role in the neural response to ischemia, hypoxia and glucose deprivation (Cheung and Hart, 2008;McCullough et al, 2005;Zhang et al, 2010). BMS-SHN753 was the most selective for tyrosine kinases e of the13 kinases that were inhibited either more strongly or to a similar degree as TrkA, 6 were tyrosine kinases e however it did inhibit several Ser/Thr kinases, including CDC like kinase 2, AuroraA and ERK8, as strongly as it inhibited Trk.…”
Section: Trk Inhibitorsmentioning
confidence: 99%